Complications and misdiagnoses associated with infant frenotomy: results of a healthcare professional survey - Mary E. O'Connor; Alison M. Gilliland; Yvonne LeFort (BMC, 2022)
Abstract Background In the past 10-15 years, there has been increased concern about ankyloglossia and its effect on infant breastfeeding. This has been associated with increased performance of frenotomy. Physicians and other healthcare professionals with expertise in breastfeeding have voiced concerns about complications related to the performance of infant frenotomy. Reviews of this topic have reported no significant complications after frenotomy. Other data on complications consist of case reports. Methods An online survey was developed by physicians with expertise in breastfeeding and e-mailed to physician and dentist members of Academy of Breastfeeding Medicine (ABM) between 11 November and 31 December 2019. It requested information from the respondents who cared for the mother/infant breastfeeding couple about their experiences personally caring for infants with complications or misdiagnoses related to referral for frenotomy or the performance of a frenotomy. Data were analyzed using chi square, Cramer's V correlation, and binomial logistic regression. Results Of 211 eligible respondents, 129 (61%) had cared for an infant with a complication or misdiagnosis. Two hundred and nine (209) infants were reported to have a complication and 237 had a misdiagnosis. The most common misdiagnoses reported were 101 of 237 infants (43%) with neuromuscular dysfunction and 65 of 237 (27%) with inadequate breastfeeding support. The most common complications reported were a repeat procedure considered/requested/performed 65 of 203 (32%) and oral aversion 57 of 203 (28%). Parental report of infant pain was associated with performance of a posterior frenotomy (Chi Square p < .003). Bleeding was associated with using scissors/scalpel vs laser/bovie/electrosurgery (Chi Square p = .001). Oral aversion was associated with performance of frenotomy by laser/bovie/electrosurgery vs scissors/scalpel (adjusted Odds Ratio of 4.05; 95% CI 2.07, 7.93). Conclusions Complications and misdiagnoses are occurring after infant frenotomy. Physicians and dentists should work closely with lactation professionals to provide skilled breastfeeding support and to evaluate for other confounding problems that might impact infant breastfeeding before referral for frenotomy. Randomized controlled trials of optimized lactation support vs. frenotomy and of scissors vs laser in performance of frenotomy are needed.